Obtenção de heteroestruturas SnO2/Nb2O5 e aplicação em sistemas de interesse ambiental - Rodrigues, Thaís Aparecida (Universidade Federal de São Carlos, 2021)
The population increase has caused several environmental problems such as contamination of aquatic bodies by organic compounds and the emission of CO2 in the atmosphere. An alternative to mitigate these impacts is Heterogeneous Photocatalysis, which is based in the use of irradiated semiconductors to oxidize organic compounds by the generation of highly oxidizing radicals, such as •OH and O2•-, or yet to reduce CO2, converting it in higher value-added products. However, a limitation is the high electron/hole (e-/h+) pair recombination rate. One way to reduce this problem is the coupling of two semiconductors in an interface in common, forming heterostructures, which allows the charge separation, prolonging their lifetime. Nb2O5 is a promising material in several fields due to its properties, including in photocatalytic processes. Additionally, it is of national interest since it can be obtained from Niobium Ammoniacal Oxalate, a byproduct from mining process. SnO2 also has physical and chemical properties suitable for applications in environmental systems. However, its energy bands do not favor its direct application in heterogeneous photocatalysis. On the other hand, the junction with Nb2O5 presents an adequate band structure for Type II heterostructure formation. This heterostructure type enables the migration of the h+ to a semiconductor, while the e- accumulates in the another, increasing the lifetime these photogenerated charge. In this work, several synthesis variables, such as precursors, synthesis temperature and time, were studied in a process based on hydrothermal treatment. The samples were characterized by XRD, Raman Spectroscopy, FTIR, DRS, SEM-EDS and SEM-FEG, N2 Fisisorção e Zeta potential. Besides that, the samples were used in different processes, such as photodegradation of organics pollutants in water, removal of contaminants via adsorption and CO2 photoreduction. The results demonstrated that the attempt to obtain Nb2O5/SnO2 heterostructures was successful, since heterostructured materials presented higher performance in different processes, when compared to isolated materials, showing the heterostructure versatility, which can be used as a single platform for the remediation of different problems.
Obtaining Nb2O5/SnO2 heterostructures and application in systems of environmental interest
Keywords: Nb2O5; SnO2; Heteroestruturas; Fotocatálise Heterogênea; Fotossíntese Artificial; Adsorção; Heterostructures; Heterogeneous Photocatalysis; Artificial Photosynthesis; Adsorption; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::TERMODINAMICA QUIMICA